Biohemijski uticaj i terapijska efikasnost laparoskopske hirurgije u ranoj fazi raka jajnika: modulacija vaskularnog endotelnog faktora rasta i tumorskih markera: Biochemical Outcomes of Laparoscopic Surgery in Early Ovarian Cancer - Han, Peng; Liu, Yafei; Han, Jin (Journal of Medical Biochemistry, 2025)
Background: The objective of this study was to investigate the biochemical impact of laparoscopic surgery on angiogenesis, focusing on vascular endothelial growth factor (VEGF), and the modulation of key tumor markers in patients with early-stage ovarian cancer.Methods: A total of 76 patients diagnosed with early ovarian cancer were enrolled and divided into two groups based on the surgical approach: the control group (n=38) underwent open surgery, and the observation group (n=38) underwent laparoscopic surgery. Surgical parameters, VEGF levels, tumor markers [matrix metalloproteinase 9 (MMP9), stromal cell-derived factor-1α (SDF-1α), and carcinoembryonic antigen (CEA)], survival rates, and incidence of complications were compared between the two groups.Results: The duration of surgery was longer in the observation group than in the control group. However, the hospitalization time, recovery of bowel function, and length of surgical incision were significantly shorter in the observation group. Intraoperative blood loss was also significantly lower in the observation group, with all differences being statistically significant (P